“I just feel like I can’t connect”: understanding targets’ organizational identification through experiences with destructive workplace behaviors - Linvill, Jennifer S. (Frontiers in Communication, 2025)
IntroductionDestructive workplace behaviors are a pervasive problem in organizations within the United States. This project aimed to make both theoretical and practical contributions focusing on individuals’ experiences as targets of destructive workplace behaviors.MethodsThis study conducted a thorough examination of how forty-nine individuals’ experiences relate to their organizational identification (i.e., connectedness). The following research question was posed: How do targets’ experiences with destructive workplace behaviors relate to their perceived organizational identification? The research examined participants’ experiences through qualitative research utilizing semi-structured interviews and provides a communicative understanding of the relationship between destructive workplace behaviors and organizational identification.ResultsData from this study provide empirical evidence that experiencing destructive workplace behaviors matters because it informs how targets identify with their organization. First, participants experienced and described a wide array of destructive workplace behaviors. Second, the relationship between destructive workplace behaviors and organizational identification varied among participants. Some participants experienced organizational disidentification while others remained identified with the organization by applying relational organizational identification tactics, including separating the organization from the perpetrator and/or connecting with trusted individuals.DiscussionFindings uncovered the tensions participants experienced between identification and disidentification to the organization and examined the ways that participants negotiated these tensions. Theoretical and practical implications are discussed.